Over a million students use our free study notes to help them with their homework
The first step is to rearrange for x: we have x=2y-3now we can plug this into the equation of the ellipse: y^2+2(2y-3)^2=39y^2-24y+15 = 0we can use the quadratic formula to solve this equation:y = (24+-sq...
Firstly, by looking at the integral, we see that this will have to be done by parts. There are 2 parts of this expression, the 'x' and the 'e^x'. As we know the formula f...
To make x the subject of the formula, we simply want to have x on its own on one side of the equals sign. So we need to remove any numbers on the same side as x. A key rule to remember is that everything ...
x = (y+12)/3
Lets begin by splitting the bx term to make factorising possible: 2x2 - x - 21 is the same as 2x2 - 1x - 21What two numbers = -1 when added, and = -42 when multiplied together?(note ...
←
444
445
446
447
448
→
Internet Safety
Payment Security
Cyber
Essentials